Investigation of changes in paraoxonase and arylesterase enzyme activities in scaly carp (Cyprinus carpio) applied oxytetracycline by bath - Aker, Ufuk; Yonar, Serpil Mise (Ege Univ, Fac Fisheries, 2020)
In this study, it was aimed to reveal the effects on paraoxonase (PON) and arylesterase (ARE) enzyme activities of oxytetracycline applied in different concentrations in scaly carp (Cyprinus carpio). For this purpose, oxytetracycline at doses of 50 and 75 mg/L was applied by bathing for 48 hours. On the 7th, 14th and 21st days after the application of oxytetracycline, liver and serum samples were taken from the fish in the control and experimental groups. Changes in the PON and ARE enzyme activities were determined in the liver and serum samples which collected from the fish. The PON and ARE activities in the liver and serum decreased in the groups exposed to oxytetracycline compared to that of the control group. This reduction was statistically different from the control group on 7, 14 and 21 days.
Keywords: Arylesterase; Cyprinus carpio; enzyme; oxytetracycline; paraoxonase